Luke’s Divine Call of Jesus. Part One - Williams, Robert Lee (Warszawskie Studia Teologiczne, 2024)
Luke represents Jesus’ death as the martyrdom of a prophet. M. Dibelius has noted this in 1919. C.H. Talbert adds in 1982 that Jesus’ death “is not an atoning sacrifice.” Such an assessment of Jesus and his death, for the “Christ” who “atones for sins,” is anemic to some scholars. F. Bovon, prefers to say, “[T]he attitude of the people . . . testifies not only to the exemplary character but also to the redemptive nature of the passion.” The question is thus joined for this paper. Was Jesus’ passion in Luke “redemptive”? The answer is found in Luke’s divine call of Jesus. Luke finds that Jesus is informed progressively of God’s plans for him on five occasions, evidently from time at prayer. The first, after his baptism (3:21b-22), reveals to him divine approval in royal and servant terminology. Next, after a night of prayer (6:12) he selects twelve as apostles and proclaims new teaching, the “Sermon on the Plain.” Then come two times of prayer (9:18, 29), the first prior to and the second on the occasion of visible transformation on a mountain, the “transfiguration,” regarding Jesus’ prophetic role and his coming suffering. After declaring at his final meal the beginning of a new covenant, but without reference to sacrifice for sins, he prays for guidance a final time on the Mount of Olives (22:41-44), preparing for anticipated suffering and vindication. We conclude that Jesus’ death for Luke is the martyrdom of a prophet that does not atone for sins but does seal a new covenant (22:20). The study will be published in two parts, the first extending through the four occasions above and the subsequent one in the issue to follow beginning with the fifth and final instance.